1996
DOI: 10.2500/105065896781794833
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of the Maxillary Sinus in Adults with Chronic Sinus Disease

Abstract: Antimicrobial therapy is a part of the care of patients with chronic sinus disease (CSD), but the etiologic role of microorganisms in this condition is unclear. Twenty patients with CSD undergoing functional endoscopic sinus surgery who had been off antibiotics for at least 1 week before surgery had a maxillary sinus aspirate for quantitative culture for aerobic bacteria and fungi and a semiquantitative culture from the antrostomy of the same maxillary sinus during endoscopic surgery. Six (30%) of the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Studies using sinus punctures have implicated anaerobic bacteria, S aureus, and H influenzae as potential pathogens. 1–5 Several recent studies using cultures of maxillary and ethmoid sinus mucosa biopsy specimens have not found a significant role for anaerobes. These more recent studies have predominantly cultured coagulase‐negative Staphylococcus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using sinus punctures have implicated anaerobic bacteria, S aureus, and H influenzae as potential pathogens. 1–5 Several recent studies using cultures of maxillary and ethmoid sinus mucosa biopsy specimens have not found a significant role for anaerobes. These more recent studies have predominantly cultured coagulase‐negative Staphylococcus.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using sinus punctures implicated Staphylococcus aureus, Haemophilus influenzae, Streptococcus pneumoniae, and anaerobes as the primary pathogens. 1–5 More recent studies, using samples obtained by swab or tissue fragments taken primarily from the nasal cavity, OMC, or maxillary or ethmoid sinuses by way of antrostomy or other surgical opening, have raised the question of Gram‐negative organisms, coagulase‐negative Staphylococcus, and even fungi as crucial pathogens. 6–10 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies in adults have shown a good correlation between cultures of the middle meatus and the sinus aspirate in patients with acute sinusitis, especially when purulence is seen in the middle meatus 164,264,270 ; however, other studies have not. 271,272 CNS is usually interpreted as a nonpathogen in acute sinusitis. Talbot et al 264 correlated the results of endoscopically obtained cultures and cultures obtained from maxillary sinus aspirates.…”
Section: Techniques For Obtaining Bacterial Culturesmentioning
confidence: 99%
“…In order to identify these microorganisms, many studies have been published in order to establish numerous variables, such as the ideal site to collect the material for culture, the best collection method, the type of material to be sent to the lab (mucosa or secretion), or the specific way to identify the microorganisms (culture or Polymerase Chain Reaction -PCR) 1,[8][9][10][11][12][13] . In recent years, many studies have tried to validate the culture done from samples collected by means of middle meatus endoscopy, and the middle meatus aspiration was investigated and established by Jiang et al (1993) 14 .…”
Section: Discussionmentioning
confidence: 99%